2020
DOI: 10.33438/ijdshs.733754
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Family-Mediated Physical Activities on Communication Skills of a Student with Autism Spectrum Disorders: A pilot study

Abstract: Effective strategies to address communication skills are critical to students with Autism Spectrum Disorder (ASD) participating in inclusive education. The purpose of this pilot study is to investigate the effects of family-mediated physical activities on the communication skills of a student with ASD. One inclusive student with ASD and his mother participated in the study designed in the pretest-posttest experimental model. For 8 weeks, family-mediated physical activities were carried out with the student wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…In the study conducted by Kurt & Arslan (2020), it was observed that participants with higher education levels exhibited higher total psychological resilience scores than those with secondary and high school education levels, and this distinction was statistically significant. Yagmur & Turkmen (2017) discovered that individuals who received education beyond high school demonstrated higher levels of psychological resilience compared to those who halted their education after high school, and this variance was statistically significant. In Bildirici's study (2014), a significant difference in psychological resilience was noted concerning education levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Kurt & Arslan (2020), it was observed that participants with higher education levels exhibited higher total psychological resilience scores than those with secondary and high school education levels, and this distinction was statistically significant. Yagmur & Turkmen (2017) discovered that individuals who received education beyond high school demonstrated higher levels of psychological resilience compared to those who halted their education after high school, and this variance was statistically significant. In Bildirici's study (2014), a significant difference in psychological resilience was noted concerning education levels.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives to promote the engagement of children with special needs in sports should be encouraged within special education and rehabilitation centers, as well as special education schools. The endeavor of children with special needs to enhance their communication with their parents through sports (Yarimkaya, Esenturk & Ilhan, 2020) and their determination to embrace life and adapt to society despite their unique circumstances can contribute to parents' increased selflessness and motivation in providing care for their children. It is crucial to investigate the factors that hinder the participation of children with special needs in sports and, if identified, take steps to eliminate these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a peer-mediated adapted physical activity program consisting of 21 training sessions was applied to a 12-year-old male individual diagnosed with autism. At the end of the training, it was reported that communication skills improved, and it contributed to his physical and cognitive development as well as his ability to communicate with peers (Yarımkaya et al, 2017).…”
Section: Weight Weeksmentioning
confidence: 99%
“…Spor ve boş zaman literatürü incelendiğinde, özel gereksinimli bireylere yönelik birçok araştırma bulunmasına rağmen (Akyıldız, 2015;Bor, 2018;Çöl, 2015;Dursun, Güler ve Mutlu Bozkurt, 2019;Esentürk ve Güngör, 2020;Kozak, İlhan ve Yarayan, 2019;Uzun, 2019;Yarımkaya, Esentürk ve İlhan, 2020;Yılmaz ve Soyer, 2018;Yılmaz ve Şahin, 2022), engelli aileleri özelinde sınırlı sayıda çalışma bulunmaktadır (Eldeniz Çetin ve Terzioğlu, 2018;Esentürk, 2021;Esentürk ve Yarımkaya, 2021;İlhan, Yarımkaya ve Esentürk, 2017;Savran, 2020;Uzunçayır ve İlhan, 2021). Ayrıca, ülkemizde özel sporcular ve ailelerine yönelik araştırma sayısının yok denecek kadar az olması bir eksiklik olarak görülmüştür (Güngör, Yılmaz ve İlhan, 2019).…”
Section: Introductionunclassified